Hydrothermal incubation-induced amyloid fibrillation of wheat gluten peptide: regulation of functional properties via multi-scale structural and morphological evolution - Yuwen Wang; Mengyuan Li; Zheng Wang; Lingfang Zhang; Binghua Sun; Sen Ma (Food Hydrocolloids, 2027)

Elucidating the mechanism of wheat bran arabinoxylan on the freeze-thaw stability of gluten protein: From the perspectives of spatial conformation and molecular polymerization of gluten protein and micro-morphology of gluten network - Mengyuan Li; Lingfang Zhang; Yuwen Wang; Xichen Lin; Xinhao Li; Li Li; Sen Ma (Food Hydrocolloids, 2026)

Integrated analysis of quality deterioration and microbial dynamics in industrial not-from-concentrate (NFC) pitaya juice during storage - Lingfang Shi; Bing Xia; Zifan Wei; Fang Wang; Jianxiu Kang; Zongren Zhao; Xinjun Du; Tiejun Li; Fuguo Xing (Food Control, 2026)

Comparative transcriptome analysis identifies ABA/ethylene signaling components and WGCNA hub genes underlying defoliant sensitivity in Gossypium barbadense - Caixia Li; Meng Wang; Zixin Zhou; Zhiqing Liu; Jianping Li; Yaohua Li; Yahui Deng; Yifan Wang; Lingfang Ran; Jiahui Zhu; Alifu Aierxi; Weiran Wang; et al. (Plant Gene, 2026)

Unveiling the impact of mixed-strain solid-state fermentation on wheat bran dietary fiber: gluten protein structure evolution, dough rheological modulation and steamed bread quality enhancement - Xinhao Li; Rui Huang; Mengyuan Li; Lingfang Zhang; Xiaojie Qian; Binghua Sun; Sen Ma; Li Li (Food Hydrocolloids, 2026)

No-tillage shapes a Sinorhizobium-centered rhizosphere network in saline-alkali soybean fields - Zhe Chen; Chuang Ma; Zhiqiang Hu; Zongling He; Jianchao Zhang; Shuyu Li; Lingfang Zhu; Xihui Shen; Baowei Bai (Plant and Soil, 2026)

Direct visual evidence of S-scheme charge transfer: CeO2 quantum dots anchored on CdS nanosheets for synergistically enhanced photocatalysis - Yaodi Fu; Ke Wen; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Environmental Research, 2026)

VALD-3 Induces GSDME-Dependent Pyroptosis via ROS/JNK/Bax Pathway in Triple-Negative Breast Cancer Cells - Xuhui Zhao; Xuhong Pan; Weijie Ma; Shuang Liang; Dezhuan Da; Jiawei Liu; LingFang Zhang; Pengfei Song; Hongling Li (Biochemical Genetics, 2026)

Silica-induced telomere dysfunction promotes pulmonary fibrosis through the activation of the cGAS-STING pathway - Qiuqian Qian; Simiao Pan; Xiaodong Li; Xiaoxue Gong; Zhaoqiang Jiang; Xing Zhang; Jianlin Lou; Lingfang Feng (Toxicology, 2026)

Integrated analysis of time-driven sensory deterioration and microbial dynamics in not-from-concentrate (NFC) pitaya juice during storage - Bing Xia; Lingfang Shi; Susu Han; Jianling Kang; Zongren Zhao; Weizhao Li; Fuguo Xing (Food Chemistry, 2026)

The influence of fulvic acid on molybdenum bioavailability assessed by Caenorhabditis elegans - Qian Huang; Lingfang Cui; Zhixin Song; Ming Li; Chao Zhang; Wenzhong Tang; Jianyin Huang (Journal of Environmental Management, 2026)

Corrigendum to “Non-monotonic effect of starch content on protein digestion in wheat noodles mediated by protein network structural changes” [Food Res. Int. 228 (2026) 118418] - Lingfang Zhang; Shuzhen Yang; Xiaojie Qian; Mengyuan Li; Sen Ma; Binghua Sun; Xiaoxi Wang (Food Research International, 2026)

Non-monotonic effect of starch content on protein digestion in wheat noodles mediated by protein network structural changes - Lingfang Zhang; Shuzhen Yang; Xiaojie Qian; Mengyuan Li; Sen Ma; Binghua Sun; Xiaoxi Wang (Food Research International, 2026)

Mineral Association and Microbial Processing Jointly Prolong Carbon Turnover in Coastal Wetlands - Yuan Li; Chuancheng Fu; Peng Ren; Zhaoliang Song; Lingfang Ni; Ting Wang; Changxun Yu; Ji Chen; Laodong Guo; Iain P. Hartley; Ding He; Xiaoguang Ouyang; et al. (Global Change Biology, 2026)
Coastal margins are critical sites for carbon (C) sequestration, yet the mechanisms stabilizing preaged, allochthonous C (externally‐derived biospheric C) in these environments remain poorly understood. Specifically, the interplay between mineral association and microbial processing represents a significant knowledge gap. Here, we investigated C sequestration mechanisms in Chinese mangrove and saltmarsh soils by analyzing topsoils and cores across 36 sites spanning a 20‐degree latitudinal transect. We found that saltmarshes, characterized by high mineral accretion and lower relative autochthonous C accumulation, exhibited significantly longer soil organic C (SOC) turnover times than mangroves (topsoils: ~2200 vs. ~500 years, respectively). This difference corresponded to higher proportions of preaged (~50%) and petrogenic (rock‐derived; ~20%) SOC in saltmarshes. Linear mixed‐effects models (LMM) confirmed that proxies for mineral protection (e.g., Al/Si) and advanced decomposition (lignin oxidation) were robust, positive predictors of turnover time across the latitudinal gradient. Further structural equation modeling (SEM) indicated a depth‐dependent shift in drivers. In surface soils, microbial necromass accumulation was a significant predictor of C turnover (coefficient = 0.36). However, at depth (1 m), the degree of lignin degradation emerged as the primary predictor of multi‐millennial C persistence (coefficient = 0.45). These results suggest a joint regulation mechanism whereby microbial processing transforms organic matter into stable forms that are subsequently protected by minerals. This mechanism effectively sequesters old, allochthonous C, challenging the paradigm that blue C storage is dominated solely by recent biomass and necessitating a reevaluation of coastal C management frameworks.

Efficient charge carrier separation over [Mo7O24]6- polyanions-intercalated porous graphitic carbon nitride for remarkably enhanced photocatalytic performance - Jiajia Liu; Yaodi Fu; Shimei Liu; Ping Li; Banpeng Cao; Lihong Cheng; Jingjing Liu; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Lingfang Qiu; Shuwang Duo (Process Safety and Environmental Protection, 2026)

Microbial abundance shapes latitudinal pattern of the greenhouse gas production potential in blue carbon ecosystems - Lingfang Ni; Chuancheng Fu; Gang Li; Kai Feng; Ye Deng; Jiaping Wu; Carlos M. Duarte; Yuan Li; Dongdong Zhang (Water Research, 2025)

Alpha-asarone relieves nasal inflammation, epithelial barrier damage, and mitochondrial damage in allergic rhinitis by inhibiting mitochondrial ROS via the SIRT1/PGC-1α pathway - Bin Xu; Weimin Gao; Haitong Li; Xiaojuan Cao; Xiaohong Chen; Nannan Dong; Lingfang Wu; Yunzhen Luo (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Genome-wide analysis of AHP genes in soybean and the role of GmAHP10 in improving salt stress tolerance - Lingfang Cao; Jinlong Cao; Li Wang; Jianjun Wang; Zhijun Che (Functional & Integrative Genomics, 2025)

Efficient biosorption of molybdenum (VI) using Chlorella pyrenoidosa biomass: Mechanistic insights and sustainable application in water remediation - Zhixin Song; Lingfang Cui; Xunan Li; Zichen Zhang; Chao Zhang; Gangfu Song; Yu Zhao; Wenzhong Tang (Journal of Cleaner Production, 2025)

Comparative analysis of microplastic and microbial communities in varied aquatic environments: Disparities in occurrence, interconnections, and ecological implications - Lingfang Fu; Yongxin Guo; Jialiang Tang; Mengdi Yang; Lu Huang; Jieer Xiao; Zhongya Fan; Zhongyang Wang; Jiangyu Zhi; Zhiwei Huang; Huaiyang Fang; Ping Li (Journal of Hazardous Materials, 2025)

Tart cherry extract alleviates gouty inflammatory response by down-regulating NF-κB signaling pathway - En Shi; Rui Wang; Lingfang Xu; Haijing Wang; Maichao Li; Kai Guo; Feng Zhang; Bingjie Liu; Yuwei He; Xianghong Meng (Food Bioscience, 2025)

Synergistic copper single sites and nanoparticles nano-trapped in hydrothermally treated Panax pseudo-ginseng for efficient CO2 transformation - Zhichao He; Lingfang Kong; Xuelin Wang; Huiwen Gong; Yunjia Li; Zixuan Lai; Zhonggao Zhou; Kan Li; Guohai Xu; Hongyu Zhen (Journal of Environmental Chemical Engineering, 2025)

Seasonal dynamics of microbial communities link to summer-autumn aquaculture disease outbreaks in Sanggou Bay - Longfei Lu; Lingfang Ni; Chunxiang Ai; Dongdong Zhang; Pengfei Zheng; Xuejing Li; Xin Liu; Hongyue Dang (Frontiers in Marine Science, 2025)
Marine microorganisms play a vital role in aquaculture by influencing water quality and the health of cultured species. Relative to conventional mono-species aquaculture, integrated multi-trophic aquaculture is more environmentally friendly and economically sustainable. However, the temporospatial dynamics of the microbial community in different aquaculture modes and their roles in the seasonal diseases of aquacultural organisms are largely unknown. Here, the seawater bacterial communities and potential pathogens were investigated over thirteen months in three different aquaculture types in Sanggou Bay, a typical maricultural area with nearly 60 years of history. Seasonality played a primary role, while aquaculture type played a subtle role in shaping the bacterioplankton community. Diverse potential pathogens were identified, and r -strategist bacteria, most of which were opportunistic pathogens and typified by Vibrio species, increased and dominated in late summer and autumn, a period of high-risk disease outbreaks in mariculture organisms. Network analyses indicated that the increase in r -strategist bacteria reduced the complexity of microbial interactions, and Vibrio halioticoli (OTU1389), a hub species with extensive positive correlations to other Vibrio OTUs, likely contributed to the increase of pathogenic vibrios due to its macroalgae degradation capability. The major potential pathogenic Vibrio OTUs were further corroborated by genome analyses and environmental simulation experiments using pathogenic Vibrio isolates, including two new species. Moreover, we found seawater dissolved oxygen, temperature, and transparency correlated significantly with the bacterioplankton temporospatial dynamics and the seasonal outbreaks of bacterial pathogens. Our results emphasize the necessity of synchronically monitoring the bacterial community, its pathogens-stimulating species, such as V. halioticoli and other macroalgae-degrading bacteria, and critical physicochemical parameters for predicting and preventing pathogen outbreaks in mariculture.

Impact of particle-attached microbial denitrification on N2O production in an agricultural-urban watershed - Mengdi Yang; Hanjie Yang; Wencai Wang; Huaiyang Fang; Lu Huang; Dan Li; Lingfang Fu; Shiyuan Ding; Xiao-Dong Li; Cong-Qiang Liu; Gangjian Wei; Dongli Li; et al. (Journal of Environmental Management, 2025)

Assessing the use of GPM DPR and IMERG products for Typhoon Mujigae over the southern coastal provinces of China - Xue Li; Lingfang Chen; Yangbo Chen; Ruihao Zhang; Zhihua Zhu; Hui Yin; Baolin Jiang (Atmospheric Research, 2025)

An exploration on the structural characteristics and antioxidant activities of casein hydrolysates fermented by Lactiplantibacillus plantarum A56 and A157 - Cuicui Duan; Lingfang Zhang; Cheng Wu; Yi Zhang; Fumin Ma; Xiaolei Li; Dan Li (Food Bioscience, 2025)

Urea interfacial polymerization-based ultra-permeable polyamide composite membrane for efficient piggery wastewater purification - Lingfang Huang; Xiaocai Cui; Huimin Dang; Yi Huang; Qian Li; Ting Ran; Xingtao Zuo; Jiajie He; Yun Zhou (Chemical Engineering Journal, 2025)

Integrated DNA methylation analysis of peripheral blood from asbestos exposed populations and patients with malignant mesothelioma reveals novel methylation driver genes of diagnostic and prognostic relevance - Lingfang Feng; Tao Li; Biao Xu; Jing Huang; Hailing Xia; Zhaoqiang Jiang; Junfei Chen; Simiao Pan; Xing Zhang; Hua Jiang; Jianlin Lou (Environmental Pollution, 2024)

S-scheme 2D/2D B-doped N-deficient g-C3N4/ZnIn2S4 heterojunction for efficient H2 production intergrated with tertracycline degradation under visible-light illumination - Jiajia Liu; Yaodi Fu; Guoliang Chu; Ke Wen; Lingfang Qiu; Ping Li; Lihong Cheng; Banpeng Cao; Yi Tang; Xiangshu Chen; Hidetoshi Kita; Shuwang Duo (Process Safety and Environmental Protection, 2024)

Comprehensive evaluation of the distribution, transport and ecological risk of heavy metals in intra-urban river sediments using high-resolution techniques - Kang Liao; Weijie Li; Zhiwei Huang; Shu Lin; Lingfang Fu; Wei Liu; Huaiyang Fang; Hong Deng (Environmental Pollution, 2024)

Exosomal proteomics and cytokine analysis distinguish silicosis cases from controls - Jiahui Yao; Yongxin Li; Shujuan Wang; Xiaowen Dong; Lingfang Feng; Xiaoxue Gong; Tiancheng Chen; Luqiao Lai; Huadong Xu; Zhaoqiang Jiang; Junfei Chen; Hailing Xia; et al. (Environmental Pollution, 2024)

Colonization characteristics and dynamic transition of archaea communities on polyethylene and polypropylene microplastics in the sediments of mangrove ecosystems - Qiong Wang; Gang Zheng; Lingfang Ni; Heng Wang; Weiye Li; Peng Guo; Yi Wang; Daoqiong Zheng; Jiaping Wu; Dongdong Zhang (Journal of Hazardous Materials, 2024)

Co-occurrence of organophosphate esters and phosphorus fractions in river sediments: Implications for pollution prediction and environment risk assessment - Lingfang Fu; Yuxin Liu; Shu Lin; Jieer Xiao; Weijie Li; Yang Yu; Hailong Zeng; Ping Li; Huaiyang Fang (Journal of Hazardous Materials, 2024)

A novel CHD7 variant in a chinese family with CHARGE syndrome - Yanhong Shan; LingFang Yao; Linli Li; Xueping Gao; Jinghan Jiang (Genes & Genomics, 2024)

Characterization of a novel endornavirus isolated from the phytopathogenic fungus Rhizoctonia solani - Yangyi Li; Xingxue Huang; Guolin Zhou; Anhua Ye; Yaohua Deng; Lingfang Shi; Runhua Zhang (Archives of Virology, 2024)

Global temperature behavior monitoring and analysis of a three-tower cable-stayed bridge - Lingfang Li; Yushi Shan; Qiang Jing; Yu Yan; Zili Xia; Yong Xia (Engineering Structures, 2023)

Higher ecological risks and lower bioremediation potentials identified for emerging OPEs than legacy PCBs in the Beibu Gulf, China - Li Zhang; Lingfang Ni; Heng Wang; Zhichao Zhang; Yichun Wu; Renming Jia; Junyu He; Zuhao Zhu; Haiyan Jin; Xing Ren; Dongdong Zhang (Environmental Research, 2023)

Hexavalent chromium [Cr(VI)]-induced ribosomal DNA copy number variation and DNA damage responses and their associations with nucleolar protein HRAS in humans and cells - Huadong Xu; Li Shi; Lingfang Feng; Fan Wu; Junfei Chen; Yao Qin; Xiaowen Dong; Zhaoqiang Jiang; Yongxin Li; Hailing Xia; Jianlin Lou (Environmental Pollution, 2023)

Photo-aging promotes the inhibitory effect of polystyrene microplastics on microbial reductive dechlorination of a polychlorinated biphenyl mixture (Aroclor 1260) - Youhua Chen; Lingfang Ni; Qing Liu; Zhaochao Deng; Jiawei Ding; Li Zhang; Chunfang Zhang; Zhongjun Ma; Dongdong Zhang (Journal of Hazardous Materials, 2023)

Yellow Petal locus GaYP promotes flavonol biosynthesis and yellow coloration in petals of Asiatic cotton (Gossypium arboreum) - Yaohua Li; Lingfang Ran; Tong Mo; Nian Liu; Jianyan Zeng; Aimin Liang; Chuannan Wang; Qingwei Suo; Zhong Chen; Yi Wang; Nianjuan Fang; Shijia Xu; et al. (Theoretical and Applied Genetics, 2023)

Bias adjustment of satellite rainfall data through Gaussian process regression (GPR) based on rain intensity classification in the Greater Bay Area, China - Xue Li; Yangbo Chen; Yueyuan Zhang; Lingfang Chen (Theoretical and Applied Climatology, 2023)

Spectral change of dissolved organic matter after extracted by solid-phase extraction and its feasibility in predicting the acute toxicity of polar organic pollutants in textile wastewater - Lingfang Fu; Liying Bin; Zhaobo Luo; Zehong Huang; Ping Li; Shaosong Huang; Dieudonne Nyobe; Fenglian Fu; Bing Tang (Journal of Hazardous Materials, 2023)

Vibration-based FRP debonding detection using a Q-learning evolutionary algorithm - Zhenghao Ding; Lingfang Li; Xiaoyou Wang; Tao Yu; Yong Xia (Engineering Structures, 2023)

Genome resequencing-based high-density genetic map and QTL detection for yield and fiber quality traits in diploid Asiatic cotton (Gossypium arboreum) - Yaohua Li; Tong Mo; Lingfang Ran; Jianyan Zeng; Chuannan Wang; Aimin Liang; Yonglu Dai; Yiping Wu; Ziman Zhong; Yuehua Xiao (Molecular Genetics and Genomics, 2022)

Evaluating the effect of midpalatal corticotomy-assisted rapid maxillary expansion on the upper airway in young adults using computational fluid dynamics - Juan Li; Lingfang Shi; Xiayao Zhang; Luxi Weng; Hong Chen; Jun Lin (Journal of Zhejiang University-SCIENCE B, 2021)

Analysing changes of the Poyang Lake water area using Sentinel-1 synthetic aperture radar imagery - Lingfang Zeng; Michael Schmitt; Lin Li; Xiao Xiang Zhu (International Journal of Remote Sensing, 2017)

Identification and molecular characterization of Panax notoginseng virus A, which may represent an undescribed novel species of the genus Totivirus, family Totiviridae - Lingfang Guo; Xin Yang; Wei Wu; Guanlin Tan; Shouguo Fang; Songbai Zhang; Fan Li (Archives of Virology, 2016)

Sphingobium endophyticus sp. nov., isolated from the root of Hylomecon japonica - Lingfang Zhu; Kaiyun Xin; Chaoqiong Chen; Changfu Li; Meiru Si; Liang Zhao; Xu Shi; Lei Zhang; Xihui Shen (Antonie van Leeuwenhoek, 2015)

Rhizobium smilacinae sp. nov., an endophytic bacterium isolated from the leaf of Smilacina japonica - Lei Zhang; Xu Shi; Meiru Si; Changfu Li; Lingfang Zhu; Liang Zhao; Xihui Shen; Yao Wang (Antonie van Leeuwenhoek, 2014)

Solirubrobacter taibaiensis sp. nov., isolated from a stem of Phytolacca acinosa Roxb. - Lei Zhang; Lingfang Zhu; Meiru Si; Changfu Li; Liang Zhao; Yahong Wei; Xihui Shen (Antonie van Leeuwenhoek, 2014)

Pseudoxanthomonas gei sp. nov., a novel endophytic bacterium isolated from the stem of Geum aleppicum - Lei Zhang; Linfang Wei; Lingfang Zhu; Changfu Li; Yao Wang; Xihui Shen (Antonie van Leeuwenhoek, 2014)

Ultrastructure and cytochemical localization of acid phosphatase of laticifers in Euphorbia kansui Liou - Xia Cai; Wei Li; Lingfang Yin (Protoplasma, 2009)